ANALYSIS OF CUSTOMARY LAW SANCTIONS IN CUSTOMARY MARRIAGE (HUMAN RIGHTS PERSPECTIVE FOR WOMEN) - Aprilia, Anisa; Akib, Ma'ruf; Umar, Wahyudi (Universitas Labuhanbatu, 2025)
This study analyzes customary law sanctions in traditional marriages, often contrary to human rights principles, especially for women. This study aims to evaluate the impact of customary law sanctions on women’s rights and provide recommendations for improvement. The method used is a qualitative approach with case studies, which involves interviews with traditional leaders and women involved in customary marriages. The results of the study show that customary law sanctions tend to burden women, creating gender injustice and human rights violations. Keywords: Customary Law; Human Rights; Woman; Penalty; Gender Equality